The effects of dietary Eleutherine bulbosa on the growth, leukocyte profile, and digestive enzyme activity of the striped catfish Pangasianodon hypophthalmus - RUDY AGUNG NUGROHO; MEYLIANAWATI MEYLIANAWATI; ODETA FEBRI ASOKAWATI; YANTI PUSPITA SARI; ESTI HANDAYANI HARDI (Smujo International, 2018)
Nugroho RA, Meylianawati, Asokawati OF, Sari YP, Hardi EH. 2018. The effects of dietary Eleutherine bulbosa on the growth, leukocyte profile, and digestive enzymes activity of Pangasianodon hypophthalmus. Nusantara Bioscience 10: 46-51. This study was conducted to examine the effects of Eleutherine bulbosa (Mill.) Urb extract (EAE) on the average weekly gain (AWG), specific growth rate (SGR), feed efficiency (FE), digestive enzyme (amylase, lipase, protease) activity, total and differential leukocyte counts, and phagocytosis activity of the striped catfish (Pangasianodon hypophthalmus). Four groups of fish with three replicates were fed 15 (P1), 30 (P2), 45 (P3), and 60 (P4) g kg-1of EAE in a basal diet and compared with control (C) fish without EAE at a rate 3% of body weight for 4 weeks. At the end of the trial, the results showed that fish fed EAE above 15 g kg-1 in the diet significantly increased AWG, while SGR, FE, lipase, protease, and neutrophil, and lymphocyte activity were not affected by any dietary concentration of EAE. The diet containing 45 g kg-1 EAE increased amylase activity in the fish while the highest number of leukocytes and phagocytosis activity was found in the fish fed 30 g kg-1 EAE in the diet. These findings suggest that the inclusion of EAE in the diet, in amounts higher than 30 g kg-1, is beneficial in improving amylase, leukocyte and phagocytosis activity of fish.